Radiation Dose Detection on FY-4B Satellite - Ying Sun; Binquan Zhang; Xiaoxin Zhang; Guohong Shen; Tao Jing; Shenyi Zhang; Xianguo Zhang; Cong Huang; Jiawei Li; Weiguo Zong; Xin Zhang; Huanxin Zhang (Aerospace, 2023)
The radiation damage effect is relatively serious during spacecraft operation in orbit. To know the real cumulative dose in orbit accurately, a radiation dose detector is carried on the FY-4B satellite. It comprises one electric control unit and three dose detectors, with a total of four payloads. Each dose detector includes five dose-monitoring points corresponding to different shielding thicknesses, which are mainly used for the measurement of the dose depth. Three dose detectors with the same function are installed in the X, Y and Z positions and can detect the total dose in different directions during the operation of the satellite. Each detector has the characteristics of small size, high integration and low power consumption. At present, the FY-4B satellite is in orbit. The detectors have been working normally since they were started up, and good preliminary detection results have been obtained. From the power-up of the detectors to April 2022, the maximum dose has reached 2.7 × 103 rad(Si). We conducted a preliminary analysis of the relationship between total dose and shielding thickness. In addition, the relationship between daily average dose and shielding thickness was further analyzed. These studies have application value for radiation protection design.